FeP nanoparticles: a new material for microwave absorption. (10th April 2018) - Green, Michael; Tian, Lihong; Xiang, Peng; Murowchick, James; Tan, Xinyu; Chen, Xiaobo
Abstract : FeP nanoparticles, fabricated through a facile thermal phosphorization process, have displayed impressive microwave absorption performance with tunable frequency and large reflection loss (RL) values. Abstract : Microwave absorbing materials play a critical role within the realms of information and homeland security in times of both peace and international conflicts; as such, discovering new materials for microwave absorption is of critical importance due to their applications in civil and military technologies. In this study, we report for the first time FeP nanoparticles as a promising material for microwave absorption. The FeP nanoparticles, fabricated through a facile thermal phosphorization process, display impressive microwave absorption performance with a reflection loss of −37.68 dB at 13.6 GHz, indicating a large absorption efficiency over 99.9%. As the thickness of the microwave absorber increases from 1.0 to 6.0 mm, the microwave absorbing peak frequency ( f max ) shifts to lower frequencies monotonically, and the critical absorbing peak width (Δ f 10 : peak width at RL = −10 dB) increases monotonically, while the reflection loss stays below −33.0 dB. This indicates a robust performance across a tunable frequency range from 8.86 to 15.1 GHz for microwave absorption. These characteristics demonstrate that FeP nanoparticles may act as a new and promising microwave absorbing material.